Book Notes [30, Fall 1992] - Palmer, Bryan D.; Kealey, Gregory S. (Labour / Le Travail, 1992)
The article briefly reviews "The Formation of Labour Movements, 1870-1914: An International Perspective," edited by Marcel Van Der Linden,and Jurgen Rojahn, "Reluctant Icon: Gladstone, Bulgaria, and the Working Classes, 1856-1878," by Ann Pottinger Saab, "On the Move: Essays in Labour and Transport History Presented to Philip Bagwell," edited by Chris Wrigley and John Shepherd, "Regulating a New Economy: Public Policy and Economic Change in America, 1900-1933," by Morton Keller, "The Nature of Work: Sociological Perspectives," edited by Kai Erickson and Steven Peter Vallas, "Repression and Recovery: Modern American Poetry and the Politics of Cultural Memory, 1910-1945," by Cary Nelson, "The Arbitration of Rights Disputes in the Public Sector," by Clarence R. Deitsch and David A. Dills, "Women, Employment and the Family in the International Division of Labour," edited by Sharon Stichter and Jane L. Parpart, "History from South Africa: Alternative Visions and Practices," edited by Joshua Brown et al., "Arbitration Discharge: Grievances in Ontario : Outcomes and Reinstatement Experiences," by Peter J. Barnacle, "Labour Arbitration Yearbook, 1991, Volume 1," edited by William Kaplan, Jeffrey Sack, and Morley Gunderson, "Class War: A Decade of Disorder," edited by Ian Bone, Alan Pullen and Tim Scargill, "Taylorism Transformed: Scientific Management Theory Since 1945," Stephen P. Waring, and "Women Workers and Global Restructuring," edited by Kathryn Ward / reviews by Bryan D. Palmer -- "Foreign Language Literature on the Nordic Labour Movements," edited by Marianne Bagge Hansen and Gerd Callesen / review by Gregory S. Kealey.
Keywords: BONE, Ian, 1956-; BOOKS -- Reviews; CLASS War: A Decade of Disorder (Book); Nonfiction; PULLEN, Alan; SCARGILL, Tim; TAYLORISM Transformed: Scientific Management Theory Since 1945 (Book); WARD, Kathryn; WARING, Stephen P.; WOMEN Workers & Global Restructuring (Book)